Endothelin-1 upregulation mediates aging-related cardiac fibrosis. (March 2015) - Wang, Xianwei; Guo, Zhikun; Ding, Zufeng; Khaidakov, Magomed; Lin, Juntang; Xu, Zhenping; Sharma, Shree G.; Jiwani, Shahanawaz; Mehta, Jawahar L.
Abstract: Endothelin-1 (ET-1) plays a major role in regulating myocardial fibrosis in several pathological conditions, such as hypertension and diabetes. Aging is an independent risk factor for myocardial fibrosis. We hypothesized that ET-1 upregulation may be a basis of enhanced collagen synthesis in the senescent fibroblasts resulting in cardiac fibrosis with aging. To examine this hypothesis, we cultured mouse cardiac fibroblasts to passage-30 (P30). β–Galactosidase activity and several other aging markers were markedly increased in P30 (vs. P3) fibroblasts, indicating that these cells were indeed undergoing senescence. Importantly, ET-1 expression was markedly upregulated in P30 (vs. P3) fibroblasts. Of note, estrogen receptor-α (ER-α), an important negative regulator of ET-1, was downregulated in P30 fibroblasts. We also studied aged (130-weeks old, female) mice hearts, and observed that ET-1 was upregulated and ER-α was downregulated in these hearts (vs. 6-week old mice hearts, female). Similar observations were made in the fibroblasts isolated from aged mice hearts. ET-1 upregulation with aging was also seen in ≈ 70-year old (vs. ≈ 30-year old) human heart sections. In concert with ET-1 upregulation, the expression of fibronectin and collagens was found to be markedly increased in P30 cardiac fibroblasts in culture, fibroblasts isolated from the aged mice hearts, and in aged human hearts. Interestingly, inhibition of ET-1 in the senescent P30 fibroblasts by 2 different strategies (the use of siRNA and the use of endothelin converting enzyme inhibitors) markedly suppressed expression of fibrosis signals. Further, treatment with synthetic ET-1 enhanced fibronectin and collagen expression in P3 cardiac fibroblasts. These observations in mice and human hearts suggest that aging-related cardiac fibrosis is, at least partially, dependent on the upregulation of ET-1. Highlights: Endothelin-1 (ET-1) is upregulated in senescent cardiac fibroblasts and aged hearts. Fibrotic signals were increased in senescent cardiac fibroblasts and aged hearts. Inhibition of ET-1 suppresses expression of fibrotic signals in the senescent fibroblasts.